Answer:
-a(a+4)/(16 - a²)
Step-by-step explanation:
a/(a - 4) Multiply by (a + 4)/(a + 4)
= a(a + 4)/[(a – 4)(a + 4)] Multiply the denominatorator terms
= a(a + 4)/(a² - 16) Multiply by -1/(-1)
= -a(a+4)/(-a² + 16) Reorder terms in denominator
= -a(a+4)/(16 - a²)
Answer:
Step-by-step explanation:
Answer:
Ok so...
Mean: 68.76
Median: 72
Range: 85
Step-by-step explanation:
Answer:
x=-2 y=3
Step-by-step explanation:
The substitution is basically given to you. Exchange x from the second equation with y-5
Once that is done and you combine the parentheses you get:
2y-10+y=-1
Add 10 on both sides of the equal sign
You get:
3y=9
Divide both sides by 3
You get:
y=3
To check your work you can substitute y in the second equation with 3 and solve it that way to get x=-2 (x equals negative two)
The first two pairs.. just substitute the x-coordinate and find y